Evolution of melts and fluids as a reflection of the crust and mantle formation by the example of the Middle Dnieper mega-block of the Ukrainian Shield. Archean - O. V. Usenko (Геофизический журнал, 2016)
The scheme of geodynamic process during the production of granite-greenstone area (GGA) of the Middle Dnieper mega-block (MDMB) of the Ukrainian Shield has been presented. It reflects the change of the lithosphere thickness during activation lasted from 3.2 to 2.8 Ga ago. Composition of fluids accompanied melts differentiation within the mantle and crust has also been described. Special features of chemical and mineral composition of the greenstone rocks structures of the Middle Dnieper mega-block are wide development of magnesia silicates and high content of iron. Peculiarities of composition of superposed alterations reflect the activity of oxidized fluids carbonate, aqueous and silicate ones. These special features are inherent to all GSS of the Archean without any exclusion and practically are never repeated later. It is possible to explain this fact by high oxidation potential at the depths of more than 100 km and water and chloride ions activity at higher levels. Granitoids and ferruginous rocks are formed during integrated geodynamic process with volcanogenic rocks of the greenstone rocks structures.